Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Is there a nice way to see that the series $$\sum_{n=0}^\infty (-1)^n (n+1)/n!$$ converges to $0$? I just did the computation numerically. Thanks

share|cite|improve this question
Hint: compute $\sum_{n=1}^N (-1)^n (n+1)/n!$. To this end, write $\sum_{n=1}^N (-1)^n (n+1)/n!$ as $\sum_{n=1}^N (-1)^n \cdot n/n! + \sum_{n=1}^N (-1)^n \cdot 1/n!$ – Yury Oct 11 '12 at 23:28
up vote 4 down vote accepted

$$\eqalign{ & \sum\limits_{n = 0}^\infty {{{( - 1)}^n}} \frac{{n + 1}}{{n!}} = \cr & = \sum\limits_{n = 0}^\infty {\frac{{{{( - 1)}^n}n}}{{n!}}} + \sum\limits_{n = 0}^\infty {\frac{{{{( - 1)}^n}}}{{n!}}} = \cr & = \sum\limits_{n = 1}^\infty {\frac{{{{( - 1)}^n}}}{{\left( {n - 1} \right)!}}} + \sum\limits_{n = 0}^\infty {\frac{{{{( - 1)}^n}}}{{n!}}} = \cr & = \sum\limits_{n = 0}^\infty {\frac{{{{( - 1)}^{n + 1}}}}{{n!}}} + \sum\limits_{n = 0}^\infty {\frac{{{{( - 1)}^n}}}{{n!}}} = - \sum\limits_{n = 0}^\infty {\frac{{{{( - 1)}^n}}}{{n!}}} + \sum\limits_{n = 0}^\infty {\frac{{{{( - 1)}^n}}}{{n!}}} = 0 \cr} $$

share|cite|improve this answer
pretty cool actually) – Alex Oct 12 '12 at 1:02

First notice that $$e^{-x}=\sum_{n=0}^\infty \frac{(-1)^nx^n}{n!}.$$ If we multiply this by $x$, we get $$xe^{-x}=\sum_{n=0}^\infty \frac{(-1)^nx^{n+1}}{n!}.$$ Now if we differentiate, we get $$e^{-x}-xe^{-x}=\sum_{n=0}^\infty \frac{(-1)^n (n+1)x^{n}}{n!}.$$ We now set $x=1$ to get $$0=e^{-1}-e^{-1}=\sum_{n=0}^\infty \frac{(-1)^n (n+1)}{n!}.$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.